Effects of Armodafinil on Simulated Driving and Alertness in Shift Work Disorder - Drake, Christopher (Sleep, 2014)
STUDY OBJECTIVES: Forty-one percent of shift workers report dozing while driving. This study tested whether armodafinil improves driving simulator performance in subjects with shift work disorder (SWD). A primary outcome was performance late in the shift when workers are typically driving home. DESIGN: Randomized, double-blind, crossover. During each 12-h test session (21:30-09:30), subjects were kept awake except for multiple sleep latency testing (MSLT: 01:30, 03:30, 05:30, and 07:30). Subjective sleepiness (Karolinska Sleepiness Scale, KSS), driving performance, and cognitive performance (digit symbol substitution test and creativity on the Remote Associates Test, RAT) were evaluated during the night shift and commute home times. SETTING: Hospital-based sleep research laboratory. PARTICIPANTS: Twenty night workers (age: 42.7 ± 8.7 y, 17 F) with excessive sleepiness (≥ 10 on the Epworth Sleepiness Scale), meeting International Classification of Sleep Disorders, Second Edition (ICSD-2) criteria for SWD, and having no other medical conditions. INTERVENTIONS: Armodafinil (150 mg) or placebo at (23:45 h) on counterbalanced nights separated by 7-14 days. MEASUREMENT AND RESULTS: Primary endpoints were driving simulator performance (standard deviation of lateral position (SDLP) and off-road deviations) with four sessions starting 3.25 h after drug administration, objective sleepiness (MSLT; 1.75 to 7.75 h post-drug), and creativity (5 h post-drug). Significant effects of drug were observed for each driving measure (P < 0.05). Armodafinil significantly improved SDLP for simulator sessions at 05:30, 07:30, and 09:30, and off-road deviations at 7 h, 15 min and 9 h, 15 min post-drug (P < 0.05). Armodafinil also improved objective sleepiness from 3.7 ± 0.6 min to 9.7 ± 5.2 min (P < 0.001) and RAT score from 8.75 ± 4.9 to 11.25 ± 6.0 (P < 0.005). CONCLUSIONS: Armodafinil 150 mg early in the night shift improves driving simulator performance in shift work disorder. Effects on sleepiness, cognition, and driving were found up to 9.5 h post-ingestion, during the critical time when many night workers are driving home. CITATION: Drake C, Gumenyuk V, Roth T, Howard R. Effects of armodafinil on simulated driving and alertness in shift work disorder. SLEEP 2014;37(12):1987-1994.